Sudden death in a patient with amyloidosis of the cardiac conduction system. - Allen, D C (1984)
A 54 year old man had generalised systemic amyloidosis secondary to bilateral basal bronchiectasis of the lungs. He died after an unexpected asystolic cardiac arrest. Necropsy showed extensive amyloid deposition in the cardiac conduction system.